Long-Term Year-Interval Effect of Continuous Maize/Soybean Intercropping on Maize Yield and Phosphorus Use Efficiency - Munir Ahmad; Tilei Zhao; Harun Gitari; Hongmin Zhao; Li Tang (Plants)
The increasing global food demand, the degradation of one-third of agricultural land, and climate change pose significant threats to food production. Maize and soybean intercropping can enhance yields and land use efficiency, yet the year-interval effects of continuous intercropping on yield, yield sustainability, and phosphorus use efficiency (PUE) remain unclear. This study evaluates the effects of continuous maize/soybean intercropping over year intervals on yield, PUE, and sustainability. A seven-year field trial (2017–2023) was conducted on acidic soil, comparing two cropping systems: maize monocropping and maize intercropped with soybean. The results showed that continuous maize/soybean intercropping outperformed maize monocropping across all year intervals. Over the first, third, and seventh year intervals, maize yield increased by 37%, 35%, and 58%, respectively, with a 55% average increase over the seven years. Intercropping also enhanced P use efficiency, as evidenced by AE, RE, PFP, and CPF increases. In the first year, AE, PFP, RE, and CPF increased by 48%, 37%, 27%, and 16%, respectively; after the third year interval, these metrics improved by 40%, 35%, 26%, and 14%; and after the seventh year interval, they rose by 60%, 58%, 24%, and 10.5%. The average AE, RE, and PFP increases over seven years were 53%, 52%, and 27%, respectively, while CPF increased by 13%. The SEM analysis further confirmed the substantial impact of the seventh year intercropping interval on maize yield, sustainability, and PUE. This study demonstrates that continuous maize/soybean intercropping can enhance maize yield, PUE, and sustainability, with the seventh year interval offering the most pronounced benefits. These findings provide valuable insights for improving food security and nutrient management challenges.